Regional Rural Banks (RRBs): Performance Analysis - Selvakumar, M. (Indian Journal of Finance, 2010)
Agriculture and rural development form an integral part of India’s development strategy, even in these days of electronic and telecommunication revolution that is having an edge over other development instruments. Rural development has been a sine qua non in the process of accelerating the pace of economic development and significantly improving the standard and quality of living of rural households. It is needless to emphasize that credit is a vital input for accelerating the pace of development of the rural economy through financing of agriculture and allied activities. Rural infrastructure and poverty alleviation programmes are meant for the weaker sections of the rural population.Majority of the rural folk are not able to meet their day-to-day requirements from their own sources of income, not to speak of investments in other productive enterprises for improving their economic conditions. Therefore, they have to depend on various financial agencies for arranging funds for making investment. Rural credit in India is a part and parcel of its economic development. Rural population is composed of agricultural producers, tenant cultivators, village artisans and landless labours. All these categories are in need of credit.